ASSESSMENT OF OPERATION AND MAINTENANCE PRACTICES IN FACILITIES MANAGEMENT OF OFFICE BUILDINGS IN LAGOS, NIGERIA - Fateye, Tosin B.; Oluwole, Toluwalase G.; Ibisola, Abayomi S.; Agbato, Samson E. (International Journal of Property Sciences (E-ISSN: 2229-8568), 2022)
The development of facility management (FM) in Nigeria is relatively new and limited in scope although it has been introduced for more than four decades. This study attempts to assess the operation and maintenance practices in the FM of office buildings from the Nigeria context, aimed to address issues concerning activities of operation and maintenance. It also intends to reveal the adoption of FM techniques and associated challenges in the office buildings in Lagos., Nigeria. A total of 216 members of the Nigerian Institution of Estate Surveyors and Valuers (NIESV) were sampled using purposive sampling techniques and their responses were analysed by descriptive statistics such as weighted mean score (WMS), severity index (S.I), and Kruskal-Wallis H test (KWT). The study found that the major FM activities that are mostly engaged include space management, power plant/electricity maintenance, waste management, lift maintenance, general cleaning services, routine maintenance, and water management. While the preferred FM technique is a blended approach (both the preventive and the corrective methods). The prominent challenges in their respective categories were design flaws and poor installation of equipment (technical); inconsistency in financing maintenance, and high cost of maintenance components (finance); weak standards and poor enforcement (administrative), indifferent attitude towards maintenance issues, wrong perception and lack of foresight (top management). The study concluded that the operations of the FM practice are still in their infancy stage and characterised by prominent challenges of technical, administrative, and finance. However, being a multi-disciplinary profession, the study suggests efficient collaborative effort can be strengthened by an institutional framework that encourages human capacity development and enhanced technology to foster sustainable facilities management practice in the country.